Narratives of older persons’ frailty and physical activity in relation to environmental landscapes and time - Payom Thinuan (2020)
© 2019 John Wiley & Sons Ltd Aims and objectives: The objective of this study was to explore the influence of the environmental landscape on the physical activity of older persons experiencing frailty. Background: This manuscript describes the second phase of an unpublished larger study in the northern province of Lampang, Thailand. Phase One revealed that 14% of 1,788 older persons surveyed were found to have experienced frailty according to Fried's frailty phenotypes, and low physical activity was associated with frailty. In the light of frailty, how older persons experience physical activity in their day-to-day living environments warrants in-depth exploration. Design: This was a qualitative study guided by narrative inquiry. Methods: In-depth interviews and observations were conducted with 13 older persons living with frailty. The method of analysis was thematic and performance analysis. Results: Two broad themes relating to the environmental landscapes were as follows: (a) limiting environmental landscapes and (b) engaging environmental landscapes. These landscapes, which change across time, refer to physical and social spaces, and beliefs of older persons and their family that have either positive or negative impacts on physical activity of frail older persons. Conclusion: Complex interactions between physical and social spaces and beliefs of older persons and family influence the physical activity behaviours of older persons living with frailty. Implications for practice: This study warrants education and policy aiming at creating optimal environmental landscapes to promote physical activity in frail older persons.